Regionalization of minimum flows in the hydrographic basin of the Rio Mearim in the state of Maranhão (Research, Society and Development, 2020)
Regionalization methods have been used to estimate flows in regions that present lack or even lack of hydrological data. Thus, the present study aimed to develop a model of regionalization of minimum flows of reference Q90 for the hydrographic basin of Rio Mearim, in the state of Maranhão. Data consisting of 28 streamflow gauge and 28 rainfall gauge were used. The variables drainage area, average annual precipitation and average monthly precipitation were used as physical-climatic characteristics of the basin under study. Regional models were developed using the Traditional Method. Validation parameters, such as the Pearson coefficient (r), the coefficient of determination (R2), the Nash-Sutcliffe coefficient (NASH), the root of the mean square error (RMSE), the mean absolute error (BIAS) and the index “c” performance indicators were used to verify the fit and performance of the models. The linear regional equation of minimum flow Q90, explained from the drainage area and average annual precipitation, was the model that showed the best performance in adjusting the observed and simulated values, being classified as good, since values of R2 and NASH greater than 0.60, as well as RMSE less than 2, BIAS equal to 0.01 and performance index (c) greater than 0.65.